Returnee CEO and innovation in Chinese high-tech SMEs. (1st January 2014) - Lin, Daomi; Lu, Jiangyong; Liu, Xiaohui; Choi, Seong-Jin
Using survey data for a sample of high-tech small and medium-sized enterprises (SMEs) in the Zhongguancun Science Park in Beijing, we examine the impact of returnee CEOs on the innovation performance of SMEs. Based on both quantitative and qualitative analyses, we find that firms with returnee CEOs are not more innovative than firms without returnee CEOs. However, returnee CEOs do have a positive impact on firms' innovation performance when they work in publicly owned firms, when they have ties with government agencies, and when their tenure as CEOs is relatively long. The findings have important implications for governments in developing countries that aim to increase their countries' innovation capability through attracting returnees and also for returnee managers who want to contribute to the innovation performance of their firms.